(untitled) (Al-Farooq Journal of Sciences, 2026)
The expression of future time in English is one of the most complex areas of English grammar because it is realized through multiple grammatical constructions rather than a single morphological future tense. English employs a variety of forms, including will, be going to, the present continuous, the simple present, and future perfect constructions, each conveying distinct semantic, pragmatic, and discourse-related meanings. This diversity presents significant challenges for learners of English as a Foreign Language (EFL), who often struggle to distinguish among these forms and use them appropriately in authentic communication. This paper examines English futurity through the complementary perspectives of Cognitive Linguistics and Functional Linguistics and explores their implications for EFL teaching and learning. Drawing on contemporary linguistic literature, the paper reviews the conceptual foundations of future-time reference and explains how cognitive processes such as conceptualization, construal, mental representation, and conceptual metaphor shape the interpretation of future expressions. It also discusses how Functional Linguistics accounts for the communicative purposes served by different future constructions in discourse. Furthermore, the paper compares these two theoretical perspectives, highlighting their complementary contributions to understanding English futurity. It identifies major challenges encountered by EFL learners, including semantic ambiguity, contextual variation, first-language transfer, and the interaction between futurity and modality. Finally, the paper proposes pedagogical strategies integrating cognitive and functional principles and outlines future research directions. It concludes that combining Cognitive Linguistics and Functional Linguistics provides a comprehensive framework for improving grammar instruction and communicative competence in EFL contexts.